(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
Forty-two fresh fecal samples from the Bengal tigers (n=30) and African lions (n=12) were collected during March 2018 to July 2018 from Bangabandhu Sheikh Mujib Safari Park, Gazipur, Dhaka. The fecal samples were processed using formol-ether concentration technique. A total of six types of parasites (egg/ cyst) were observed viz.; one protozoan (Coccidia spp.), two cestodes (Hymenolepis spp., and Diphyllobothrium spp.) and three nematodes (Ascaris spp., Toxocara spp. and hookworms). No trematodes were found during the study. Occurrence of gastrointestinal (hereafter GI) parasites recorded in tigers was 90% (n=27/30) and lions was 100% (n=12/12). The highest prevalence was of Coccidia spp. (85.71%) followed by Diphyllobothrium spp. (42.86%), Hymenolepis spp. (28.57%), Ascaris spp. (21.43%), Toxocara spp. (14.29%) and hookworms (14.29%). The prevalence of protozoans (85.71%) was higher than that of helminths (78.57%) in the hosts. On the basis of intensity of parasites, male carnivores were more susceptible to infection than females. The intensity of infection was higher in young ones as compared to adults. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 27-32